Helically twisted long-period fiber gratings of YOFC single-mode fiber with optical fiber welding machine - Bai, Yunfeng; He, Zelong; Bai, Jiyuan; Dang, Suihu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
The single-mode fiber provided by YOFC inc is employed for spiral processing by commercial welding machine. It can clearly see the periods structure under the light, but there is no obvious deformation of the fiber core, cladding and surface morphology under a microscope. There is an obvious resonant peak near 1560 nm, half peak width is about 25 nm, the depth of the resonant peak closed to –26 dB, when the period is about 411 μm. It agrees with theoretical calculation results according to the long-period fiber grating coupled-mode theory. The resonance wavelength is caused by coupling between the fundamental mode and the LP14 mode. The responsivities of the helically twisted long-period fiber gratings (H-LPFG) for the temperature is measured, the resonance wavelength is linear with temperature, the slope is 86 pm/℃. Because it is easy to inscribe by commercial welding machine, and has a strong resonance peak, it has potential applications as the temperature sensor.
Optica Applicata, Vol. 51, 2021, nr 3, s. 407-413
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; YOFC single-mode fiber; helically twisted long-period fiber gratings; fundamental mode; cladding mode; coupled-mode theory